Bone Conduction Hearing System And Open Source Application: One alternative for patients with hearing loss - Flor, Omar Cristobal (2021)
n this work, a low-cost hearing assistance system is presented withthe use of conventional type skin-operated bone conduction head-phone designs, created with technology by deposition of moltenmaterial in a 3D printer and use of an audio receiver from cellulardevices. Sound is captured, processed and filtered for later transmis-sion to the designed hearing aids. This alternative was created toassist children with moderate-grade conductive hearing loss. Thesystem, for its use, uses an open source application "UYARINA". Thecharacteristics of the system, the designed headphones, the appli-cation developed, the results and its performance tests in childrenbetween 8 and 12 years old are presented